Gone Crazy in Alabama - Rita Williams-Garcia (Amistad - Harper Collins Publishers, 2016)
Delphine, Vonetta, and Fern are off to Alabama to visit their grandmother Big Ma and her mother, Ma Charles. Across the way lives Ma Charles$1 (Bs half sister, Miss Trotter. The two half sisters haven$1 (Bt spoken in years. As Delphine hears about her family history, she uncovers the surprising truth that$1 (Bs been keeping the sisters apart. But when tragedy strikes, Delphine discovers that the bonds of family run deeper than she ever knew possible.Powerful and humorous, this companion to the award-winning One Crazy Summer and P.S. Be Eleven will be enjoyed by fans of the first two books, as well as by readers meeting these memorable sisters for the first time.s
Keywords: Historical Fiction -- Historical Fiction